Pendampingan Penggunaan Media Literasi Kreatif dalam Pembelajaran bagi Guru SMA - Talitha Afifah; Aris Fatunnisa; Ingghar Ghupti Nadia Kusmiaji; Lirva Ninda Rosyidah; Sarah Bunga Srikandi Wati (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Learning in high schools requires innovation to optimally improve students' literacy skills. However, many teachers still do not utilize creative literacy media in the learning process, resulting in less interactive learning activities and less encouragement of active student participation. Therefore, this community service activity aims to provide guidance on the use of creative literacy media for teachers at SMA Muhammadiyah 1 Pare. The implementation method is carried out through material delivery, training, practice using literacy media, and assistance in designing learning media. The activity is carried out in the form of workshops and interactive discussions so that participants can understand the concepts and practices directly. The results of the activity indicate that teachers gain a better understanding of the use of creative literacy media and are able to develop learning media that are more varied, interesting, and encourage active student participation in the learning process.